Pengaruh Kecerdasan Emosional dan Literasi Digital terhadap Kinerja Pegawai Generasi Z Studi Kasus pada Dinas Kependudukan dan Pencatatan Sipil (DUKCAPIL) Kota Bima - Eni Muliyani; Firmansyah Kusumayadi; Khairul Ammar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to determine whether emotional intelligence and digital literacy have a positive and significant effect on the performance of Generation Z employees in Bima City. This is a quantitative, associative study. The population consists of all Generation Z employees in Bima City, with a sample size of 99 employees. Purposive sampling based on specific criteria was employed. Data were collected using a Likert-scale questionnaire and analyzed via multiple linear regression using SPSS version 21. The results indicate that: 1) emotional intelligence has a positive and significant effect on the performance of Generation Z employees in Bima City; 2) digital literacy has a positive and significant effect on the performance of Generation Z employees in Bima City; and 3) emotional intelligence and digital literacy have a positive and significant effect on the performance of Generation Z employees in Bima City.